Pengaruh Pemberian Konseling Tanda-Tanda Bahaya Kehamilan Terhadap Pengetahuan Ibu Hamil Di Puskesmas Kamonji Kota Palu - djaroh , Siti; asparika, novi (Akademi Kebidanan Palu Sulawesi Tengah, 2019)
According to a report from WHO, maternal deaths generally occur due to complications during and after pregnancy. It is known that about 75% of the total cases of maternal death are caused by complications such as bleeding, infection, high blood pressure during pregnancy, complications of labor, and unsafe abortion. Besides being caused by pregnancy complications, the lack of knowledge of mothers regarding complications during pregnancy is also a contributing factor to the maternal mortality rate. Furthermore, the researchers conducted an initial case study by measuring the level of knowledge of mothers who had been counseled at the Kamonji health center, from 4 pregnant women. It turned out that 2 pregnant women (50%) had bad knowledge about pregnancy danger signs such as nausea and excessive vomiting and ruptured membranes. early. The purpose of this study is to know the effect of giving counseling about the danger signs of pregnancy to the knowledge of pregnant women in the kamonji health center. The design of this analytical study is comparative. The sample size is 43 people, before being given counseling good knowledge as many as 37 people (86%), lack of knowledge as many as 6 people (14%). After being given counseling, there were 43 people who had good knowledge (100%), while those with less knowledge were nonexistent (0%). The conclusion is the influence of giving counseling to the knowledge of pregnant women. Counseling about the danger signs of pregnancy is very important to be known by pregnant women so that it can be immediately possible to prevent pregnant women from experiencing complications / high risk and reduce MMR.